InSEA Project: Initiatives in Supporting the Consolidation and Enhancement of the EMSO Infrastructure and Related Activities - De Santis, Angelo; Chiappini, Massimo; Marinaro, Giuditta; Guardato, Sergio; Conversano, Fabio; D’Anna, Giuseppe; Di Mauro, Domenico; Cardin, Vanessa; Carluccio, Roberto; Rende, Sante Francesco; Giordano, Raffaele; Rossi, Lorenzo; et al. (Frontiers in Marine Science, 2022)
The InSEA project ("Initiatives in Supporting the consolidation and enhancement of the EMSO research infrastructure consortium (ERIC) and related Activities") has the objective, as the full name of the project indicates, to consolidate and strengthen the infrastructures concerning the EMSO (“European Multidisciplinary Seafloor and water column Observatory”) ERIC (European Research Infrastructure Consortium) and all those technical-scientific activities related to it. In particular, the project is upgrading localized and distributed marine infrastructures, laboratories, observatories and spatial measurement activities in Southern Italian seas to support those activities of surveys in fixed time series points of observation of EMSO ERIC. The project is developing according to six implementation Objectives of Research (OR) that involve four National research Institutions: INGV, ISPRA, OGS and Anton Dohrn Zoological Station of Naples. The paper illustrates with more details the relevant objectives of the InSEA project and its most significant implementation phases.